85/792
Пошаговое объяснение:
1) В первых скобках:
9 + 3 3/8 = 12 3/8
2) Во вторых скобках:
4 2/9 - 3 5/11 = (4-3) + (2/9 - 5/11) = 1 + [(2·11) - (5·9)]/99 = 1 +((22-45)/99) = 1 - 23/99 = 99/99 - 23/99 = 76/99.
Можно по-другому (результат будет такой же):
4 2/9 = 38/9
3 5/11 = 38/11
38/9 - 38/11 = 38 · (1/9 - 1/11) = 38 · (11/99 - 9/99) = 38 · (2/99) = 76/99.
3) Теперь всё вместе:
13 1/4 - 12 3/8 - 76/99 = (13 2/8 - 12 3/8) - 76/99 = (1 - 1/8) - 76/99 = 7/8 - 76/99 = 7 · 99/792 - 76·8/792 = 693 /792 - 608/792 = 85/792 ≈ 0,1073 ≈ 0,11
ответ: 85/792 ≈ 0,11
85/792
Пошаговое объяснение:
1) В первых скобках:
9 + 3 3/8 = 12 3/8
2) Во вторых скобках:
4 2/9 - 3 5/11 = (4-3) + (2/9 - 5/11) = 1 + [(2·11) - (5·9)]/99 = 1 +((22-45)/99) = 1 - 23/99 = 99/99 - 23/99 = 76/99.
Можно по-другому (результат будет такой же):
4 2/9 = 38/9
3 5/11 = 38/11
38/9 - 38/11 = 38 · (1/9 - 1/11) = 38 · (11/99 - 9/99) = 38 · (2/99) = 76/99.
3) Теперь всё вместе:
13 1/4 - 12 3/8 - 76/99 = (13 2/8 - 12 3/8) - 76/99 = (1 - 1/8) - 76/99 = 7/8 - 76/99 = 7 · 99/792 - 76·8/792 = 693 /792 - 608/792 = 85/792 ≈ 0,1073 ≈ 0,11
ответ: 85/792 ≈ 0,11